CONFLICTS OVER VARIOUS VALUES – THE ROLE OF IDENTITY IN CONFLICT (Annual of the Faculty of Philosophy in Skopje, 2022)
Among the numerous causes of conflicts in today’s security environment, conflicts over various values occupy an important place in the security agenda. Experience and researches so far, show that these conflicts initiate a different, very sensitive way of reacting between the conflicting parties. This, in turn imposes a necessity of comprehensive as well as cautious approach in their management and resolution. Given the fact that the value system is being formed throughout life, both through broader cultural and social influences and through our own experience, the paper explores the role of identity in conflicts over various values. Specifically, the research focus is based on the analysis of situations, reasons and ways in which identity can be a cause or trigger for the emergence or escalation of the so-called identity-based conflict. In this context, the paper specifically explores the impact and role that identity can play at different stages in conflicts over various values, with a particular focus on conflicts with ethnic-identity characteristics.
Keywords: identity; ethnic group; threat; violence; conflict